Exploring the Orton-Gillingham Approach to Teaching Reading from the Perspective of Tutors at the Scottish Rite Learning Centre for Children - Halifax - Heather Hollis; Mary Jane Harkins (Language and Literacy: A Canadian Educational e-journal)
Research indicates that individuals with poor reading skills are more at risk of dropping out of school and having fewer career options than their peers who are proficient readers (Castles at al., 2018; Jamieson, 2009). The Scottish Rite Learning Centre for Children - Halifax (SRLCC-H) in Nova Scotia offers tuition-free tutoring services based on the Orton-Gillingham approach, to students with reading-based learning disabilities, such as dyslexia. Through individual interviews, this study explores the perspectives and experiences of the volunteer tutors and tutors-in-training at the SRLCC-H. The findings indicate that OG tutoring improved their students’ reading abilities and increased their levels of confidence.